Breeding male mole-rats (Fukomys) use strong bites to defend reproductive monopoly - Šumbera, Radim; Kraus, Andrea; Mikula, Ondřej; Okrouhlík, Jan; Measey, John; Begall, Sabine; Bennett, Nigel C; Zöttl, Markus; Herrel, Anthony; Lövy, Matěj (Communications biology, 2025)
Bite force is a simple trait indicating an animal's performance related to foraging, social dominance, and defence, all of which influence individual reproductive success. We examine the effect of breeding status on bite force in four social species of Fukomys, a genus of subterranean African rodents (Bathyergidae). These species are cooperative breeders, where reproduction is limited typically to a breeding pair. We collected in vivo bite force data, head width, and upper incisors width from 404 individuals from 75 families and tested whether breeders exhibit stronger bite force. We reveal that breeding males of all four species outperform non-breeders, with bite force in non-breeding males and females being 12% and 22% lower, respectively. In contrast, breeding females underperform relative to other categories, with bite force approximately 31% lower than in breeding males, and many are reluctant to bite. Head width and upper incisors width corroborate these findings. We propose that breeding males require a stronger bite force because of repeated competition with non-related males that may try to enter the family. In contrast, there is much less competition for the breeding position among females, as females rarely intrude into established families.
Keywords: mikroftalmičtí podzemní hlodavci; Mole Rats; síla skusu; ženské pohlaví; zvířata; Sexual Behavior, Animal; Breeding; chov; mužské pohlaví; Animals; rozmnožování; sexuální chování zvířat; Reproduction; Male; Female; Bite Force